PENGARUH WORK LIFE BALANCE DAN KETERIKATAN PEGAWAI TERHADAP KINERJA PEGAWAI FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS INDONESIA - Maya Sarikit (Jurnal Manajemen Pendidikan, 2017)
The objective of the research is to obtain information about the influence of work life balance and employee engagementon employees job performance onFaculty of Social and Political Sciences of the University of Indonesia .The research was conducted to all of employees onFaculty of Social and Political Sciences of the University of Indonesia by using a survey method with path analysis applied in testing hypothesis. The number 67 employees as sample was selected by using Slovin formula. The result of the study reveals that: (1) there is direct effect of work life balance on job performance. (2) there isdirect effect of employee engagement on job performance. (3) there is direct effect of work life balance on employee engagement. Therefore to enhance employee’s job performance can be carried out by work life balance, and employee engagement.